End losses minimization of linear Fresnel reflectors with a simple, two-axis mechanical tracking system. (1st April 2018) - Yang, Moucun; Zhu, Yuezhao; Taylor, Robert A.
Graphical abstract: Highlights: End losses of LFR were modeled, simulated and experimentally analyzed. A new two-axis tracking system for LFR is designed to compensate for end losses. The optimal d s, lim and ( L / H )lim are fitted to show when and where it can be used. The optical efficiency can be improved by 8–50%, depending on L / H and latitude. The two-axis LFR system is beneficial for space-limited, industrial applications. Abstract: In order to compensate for end losses in linear solar concentrators (which can account for 33% of the optical losses), a mechanically simple two-axis tracking system was designed and analyzed. In the proposed system, a standard linear Fresnel reflector (LFR) with east-west rotational tracking was placed on north-south rails and driven by a linear actuator. By keeping the receiver fixed, end losses can be eliminated when the reflector slides along the rails. The relative optical efficiency improvement of this design was studied in detail though a combination of theory, numerical simulation, and experimentation. The results show that the annual average optical efficiency of an LFR can be improved by 8–50%, depending on the normalized collector length and local latitude. The optimal sliding distance limit, d s, lim, and the LFR geometries where this design is most techno-economically beneficial were also investigated. It was found that the proposed tracking system is most applicable to solar-driven, industrial process heat systems where rooftop or ground space is limited.